Improvement of local ozone phytotoxicity modelling for autochthonous grape cultivars - Blanco-Ward, Daniel (2023)
Cervical cancer prevention is based on primary prevention with vaccines against Human Papillomavirus (HPV) and secondary prevention by screening with High-Risk-HPV (Hr-HPV) detection. Since 2017, cervical cancer screening in women aged 25-60 years has been performed in Portugal using Hr-HPV detection, followed by cytology in Hr-HPV-positive cases. Herein we report the prevalence of Hr-HPV genotypes and cytological abnormalities among 462401 women (mean age: 43.73 +/- 10.79; median age: 45; range: 24-66 years) that participated in the Regional Cervical Cancer Screening Program of the Northern Region of Portugal, performed between August 2016 and December 2021. Overall, we describe a prevalence rate of 12.50% for Hr-HPV varying from 20.76% at age 25% to 8.32% at age 64. The five most common Hr-HPV genotypes identified were HPV-68 (16.09%), HPV-31 (15.30%), HPV-51 (12.96%), HPV-16 (11.06%), and HPV-39 (11.01%). The prevalence of Hr-HPV included in the nonavalent vaccine (HPV-9valent) was 55.00% ranging from 47.78% to 59.18% across different age groups. Considering positive Hr-HPV cases, 65.68% had a Negative for Intraepithelial Lesion or Malignancy (NILM) cytology, 20.83% atypical squamous cells of undetermined significance (ASC-US), 8.85% Low-Grade Squamous Intraepithelial Lesion (LSIL), 1.65% High-Grade Squamous Intraepithelial Lesion (HSIL), 2.85% ASC-H, 0.09% Atypical Glandular Cells, 0.02% Adenocarcinomas, and 0.02% Squamous Cell Carcinoma (SCC). Our analysis revealed that HPV-9val genotypes were responsible for 52.13% NILM, 59.21% ASC-US, 55.06% LSIL, 90.14% HSIL, 83.50% ASC-H, and 100.00% SCC. Furthermore, multiple Hr-HPV infections (risk ratio [RR] = 1.46; 95% confidence interval [CI] 1.34-1.58), HPV-16/18 (RR = 5.16; 95% CI 4.75-5.93), or HPV-9val genotypes (RR = 5.23; 95% CI 4.68-5.85) were associated with a significant risk of developing > HSIL (p < 0.001). To date, this is the largest study on Hr-HPV genotyping in cervical cancer screening that includes data from a complete cycle of the screening program. Our findings suggest a high prevalence of HPV-9valent genotypes and a significant association with an increased risk of developing > HSIL. This constitutes important data for health authorities, which may help define the future of vaccination and cervical cancer screening strategies.